No point B : new rules for leading change in the hyper-connected radically-conscious economy - Gardner, Caleb, 1982- (Ascent Audio, 2022)
Our future depends on changing the way we change. But because technology has forever altered our relationship with what's coming next, the tomorrow we envisioned is too often totally different by the time it arrives. How can leaders manage disruption when disruption never stops coming? Drawing upon his vast experience in business leadership and social activism, author Caleb Gardner shows how the simple idea of embracing constant change as a core competency for living in a complex world could revolutionize our relationship with modernity and transform our approach to effective leadership. Through stories from his career and advice from experts in sociology, psychology, and management, No Point B proposes nine principles for mobilizing the next generation of effective change leaders, including: focusing on effective communications to navigate our reality-distorting media, building adaptive capability and tackling cross-disciplinary problems, and never resting on our assumptions about how to best navigate the world. The only way we'll make significant progress on building a better world is by recognizing better is a process of constant adaptation, not an end point.